2010
DOI: 10.1007/s12078-010-9067-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Food Color Influence Taste and Flavor Perception in Humans?

Abstract: In this paper, we review the empirical literature concerning the important question of whether or not food color influences taste and flavor perception in humans. Although a superficial reading of the literature on this topic would appear to give a somewhat mixed answer, we argue that this is, at least in part, due to the fact that many researchers have failed to distinguish between two qualitatively distinct research questions. The first concerns the role that food coloring plays in the perception of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
278
2
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 424 publications
(319 citation statements)
references
References 115 publications
(271 reference statements)
12
278
2
3
Order By: Relevance
“…Indeed, certain other types of crossmodal correspondences (e.g. the correspondence between redness and sweet taste) appear to result from the internalization of the statistical properties of the environment (i.e., red fruit are often ripe and sweet; Spence, Levitan, Shankar, & Zampini, 2010) in a Hebbian type of learning (Hebb, 1949)-a mechanism that comes with apparent benefits for object recognition and most likely individual survival. The adaptive reasons for robust sound-taste associations, in contrast, are less clear (similar to sound-smell correspondences; see Deroy, Crisinel, & Spence, 2013).…”
Section: Are Crossmodal Correspondences Between Sound and Taste Cultumentioning
confidence: 99%
“…Indeed, certain other types of crossmodal correspondences (e.g. the correspondence between redness and sweet taste) appear to result from the internalization of the statistical properties of the environment (i.e., red fruit are often ripe and sweet; Spence, Levitan, Shankar, & Zampini, 2010) in a Hebbian type of learning (Hebb, 1949)-a mechanism that comes with apparent benefits for object recognition and most likely individual survival. The adaptive reasons for robust sound-taste associations, in contrast, are less clear (similar to sound-smell correspondences; see Deroy, Crisinel, & Spence, 2013).…”
Section: Are Crossmodal Correspondences Between Sound and Taste Cultumentioning
confidence: 99%
“…Effects of the joint presentation of olfactory and visual cues In the case of olfaction and vision, for instance, it is well established that semantically congruent visual shapes-but also colors in general-facilitate olfactory identification (see, e.g., Demattè et al, 2009; see also Spence, Levitan, Shankar, & Zampini, 2010, for a review for a review of orthonasal and retronasal olfaction). Interestingly, Zellner and Whitten (1999) reported that while semantically congruent colors can enhance the intensity of a perceived odor (green for mint odor, red for strawberry odor), the effect was mainly due to the intensity of the color, while hue had little effect: The presence or absence of color in the concurrently presented solution seems to be an important factor (see also Zellner, Bartoli, & Eckard, 1991;Zellner & Kautz, 1990; but see , in addition to whether it was red or green.…”
Section: Underevidenced Behavioral Effectsmentioning
confidence: 99%
“…Lyman (1989, p. 112) That said, colour contrast cannot so easily be used to explain the effects of coloured bowls reported by Harrar et al [16] because the popcorn was eaten by hand and would therefore likely always have been seen against a constant colour background (the participant's hand) just before being put into the participant's mouth. However, an alternative possibility here is that their effects demonstrate another example of sensation transference, given that red is typically associated with sweetness while blue is more often associated with saltiness [21,22,23]. As to where such colour-taste associations come from, consumers may simply be attuned to the statistics of the environment [21]; and/or to the packaging and product colouring typically used in the supermarket [23,24].…”
Section: Cutlerymentioning
confidence: 99%
“…However, an alternative possibility here is that their effects demonstrate another example of sensation transference, given that red is typically associated with sweetness while blue is more often associated with saltiness [21,22,23]. As to where such colour-taste associations come from, consumers may simply be attuned to the statistics of the environment [21]; and/or to the packaging and product colouring typically used in the supermarket [23,24]. Evolutionarily-speaking, it would certainly make sense to be able to pick-up on the natural correlations that exist between colour and flavour in order to predict which foods would be riper, sweeter, and hence more likely to be rich in energy (imagine choosing fruit on a tree).…”
Section: Cutlerymentioning
confidence: 99%